Literature Review for Research Design - Govil, Kailash C.; Verma, Anjali (Indian Forester, 1997)
Literature review follows the justification of research objectives, the first stage of any research design and improves legitimacy, credibility and efficiency to any research work. It helps in identifying relevant past work, methods and conclusions for developing concise and clear context of the problem, hypothesis, methods, analysis and inference drawing for the proposed research work i.e. framing an appropriate research design and avoiding duplication of efforts. The review of literature can be divided into four important steps : identification and collection; evaluation; selection and finally credit to past research work. The secondary information provided by the literature review may be used to supplement the primary information, improve data collection, analysis and therefore the efficiency of any research design. Increased and regular use of literBture review may initially contain and later resolve many problems related to quality and efficiency of forestry research. After going through the available literature, the researcher can eventually see his! Her research problem and its context in a new light and if need be, even redefine the justification of his/her research objectives. The different stages of the research design are linked through a loop and therefore at every stage the researcher should go through this loop.